The Image of Poles in the Selected Works of V. P. Astafiev. Imagological Analysis - Wawrzyńczak, Aleksander (Literatūra, 2025)
The article analyses the image of Poles in selected works of Viktor Petrovich Astafiev, a classic of Russian literature of the twentieth century. The subject of the analysis is works from two cycles of the writer – The Last Tribute and Zatesi. Astafiev’s image of Poles is connected both with his childhood memories and his military experience. The research revealed a number of distinctive features of Poles especially highlighted by Astafiev: patriotism and adherence to national religious traditions, diligence and honesty. In the story “The Opening of the Church”, describing his accidental presence in 1977 at the opening of a new church in a working-class neighbourhood of Kraków by Cardinal Karol Wojtyla, Astafiev expressed a unique respect shown in the Russian literature to the achievements of this Catholic priest who later became Pope John Paul II. He also appreciated the Poles for their consistent resistance against communist totalitarianism, seeing him as a role model.
Keywords: Viktor Astafiev; Poles; imagology; heteroimage; autoimage